14. Simplify:
![( \frac{ \sqrt{5 - 1} }{ \sqrt{5 + 1} } + \frac{ \sqrt{5 + 1} }{ \sqrt{5 - 1} } ( \frac{ \sqrt{5 - 1} }{ \sqrt{5 + 1} } + \frac{ \sqrt{5 + 1} }{ \sqrt{5 - 1} }](https://tex.z-dn.net/?f=%28+%5Cfrac%7B+%5Csqrt%7B5+-+1%7D+%7D%7B+%5Csqrt%7B5+%2B+1%7D+%7D++%2B++%5Cfrac%7B+%5Csqrt%7B5+%2B+1%7D+%7D%7B+%5Csqrt%7B5+-+1%7D+%7D+)
Answers
Answered by
1
Question:-
Simplify:
Solution:-
We have,
Substitute
= ![\frac{2}{ \sqrt{6} } + \frac{ \sqrt{6} }{2} \frac{2}{ \sqrt{6} } + \frac{ \sqrt{6} }{2}](https://tex.z-dn.net/?f=+%5Cfrac%7B2%7D%7B+%5Csqrt%7B6%7D+%7D++%2B++%5Cfrac%7B+%5Csqrt%7B6%7D+%7D%7B2%7D+)
= ![\frac{(2 \times 2) + (\sqrt{6} \times \sqrt{6}) }{2 \sqrt{6} } \frac{(2 \times 2) + (\sqrt{6} \times \sqrt{6}) }{2 \sqrt{6} }](https://tex.z-dn.net/?f=+%5Cfrac%7B%282+%5Ctimes+2%29+%2B++%28%5Csqrt%7B6%7D++%5Ctimes++%5Csqrt%7B6%7D%29+%7D%7B2+%5Csqrt%7B6%7D+%7D+)
= ![\frac{4 + 6}{2 \sqrt{6} } \frac{4 + 6}{2 \sqrt{6} }](https://tex.z-dn.net/?f=+%5Cfrac%7B4+%2B+6%7D%7B2+%5Csqrt%7B6%7D+%7D+)
= ![\frac{10}{2 \sqrt{6} } \frac{10}{2 \sqrt{6} }](https://tex.z-dn.net/?f=+%5Cfrac%7B10%7D%7B2+%5Csqrt%7B6%7D+%7D+)
= ![\frac{5}{ \sqrt{6} } \: \: (or) \: \: \frac{5}{ \sqrt{5 + 1} } \frac{5}{ \sqrt{6} } \: \: (or) \: \: \frac{5}{ \sqrt{5 + 1} }](https://tex.z-dn.net/?f=+%5Cfrac%7B5%7D%7B+%5Csqrt%7B6%7D+%7D++%5C%3A++%5C%3A+%28or%29+%5C%3A++%5C%3A++%5Cfrac%7B5%7D%7B+%5Csqrt%7B5+%2B+1%7D+%7D+)
Similar questions